Persepsi Masyarakat terhadap Kinerja Pelayanan dalam Program Percepatan Peningkatan Cakupan Kepemilikan Dokumen Kependudukan di Kabupaten Klungkung - Dharmanu, I Putu; Wijaya, Komang Adi Sastra (Universitas Medan Area, 2019)
Klungkung Regency as one of the regencies in Bali that has land and islands, the problem faced is the low coverage of ownership documents. Therefore, the Klungkung Regency Population and Civil Registry Service implements the Program to Accelerate Increasing Scope of Population Document Ownership, the policy being an innovative step in overcoming population services in Klungkung Regency. Based on these problems, in this study we want to analyze community perceptions of service performance in the P3CKDK in Klungkung Regency. The method used in this study is the mix methods, namely using quantitative methods in public perception then proceed with qualitative methods to explore existing data. Based on the results of the analysis show that the service performance that gets the highest public response (tends to strongly agree) is the empathy index. While other indices in service performance also received a positive response from the public. Furthermore, public perceptions related to program performance from various indices tended to strongly agree. The index that gets the highest rating is the program access index. Correlation between service performance and program performance results in a positive correlation which means that if one indicator increases the associated indicator will also increase. Based on the tests conducted, it shows that service responsiveness with program performance produces the highest correlation, while the lowest correlation is assurance with program performance.